Effect of Short-Term Kinesiology Taping on Knee Proprioception and Quadriceps Performance in Healthy Individuals - Wei, Zhen; Wang, Xiao-Xi; Wang, Lin (Frontiers in Physiology, 2020)
Background: Kinesiology taping (KT) is well known measure for preventing musculoskeletal injuries. Our study aims to explore the actual effects of KT on healthy participants’ knee proprioception and quadriceps performance within 1 hour. Methods: A total of 35 healthy male amateur runners were recruited in our study. Four taping sequences were randomly allocated to four different weeks, namely, no taping, placebo taping, KT with tension and KT with no tension. A CON-TREX isokinetic dynamometer was used in assessing the participants’ knee proprioception and muscle strength of knee extension and flexion at 60°/s. The electromyography (EMG) signals of medial oblique muscle and vastus lateralis were collected using Myon EMG system synchronously. Two-way repeated measures ANOVA was used in exploring the difference between taping and time effect, and the significance was set to alpha < 0.05. Results: Significant interaction effect was found between the taping groups and time effect (F [3.32] = 2.389, P = 0.029, η2 = 0.050) in the peak torque during the concentric contraction of quadriceps. No significant interaction and no significant differences between groups and time effects in knee proprioception and muscle activation. Conclusion: The effect of KT seems insufficiently large to impose a positive effect on healthy people within short periods. Health participants may not necessary use KT to increase muscle activation and proprioception of knee.